Resistance of amphiphilic polysaccharides against marine fouling organisms - Bauer, Stella; Alles, Maria; Arpa Sancet, Maria Pilar; Ralston, E.; Swain, G. W.; Aldred, N.; Clare, A. S.; Finlay, J. A.; Callow, M. E.; Callow, J. A.; Rosenhahn, Axel (Biomacromolecules, 2016)
Amphiphilic coatings are promising candidates for fouling-release applications. As hydrophilic components, polysaccharides are interesting and environmentally benign building blocks. We used covalently coupled alginic acid (AA) and hyaluronic acid (HA) and postmodified them with a hydrophobic fluorinated amine. The surfaces showed good stability under marine conditions and fluorination led to a decreased uptake of Ca2+ ions after modification. In single species settlement assays (bacteria, diatoms, barnacle cypris larvae), the modification decreased the settlement density and/or the adhesion strength of many of the tested species. Field studies supported findings of the laboratory experiments, as hydrophobic modification of AA and HA decreased diatom colonization.
Gesehen am 23.04.2020